2018
DOI: 10.1080/01616846.2018.1511214
|View full text |Cite
|
Sign up to set email alerts
|

Do digital devices enhance teenagers’ recreational reading engagement? Issues for library policy from a recent study in two Australian states

Abstract: Do digital devices enhance teenagers' recreational reading engagement? Issues for library policy from a recent study in two Australian states

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Adolescents noted that the smartphone could be distracting and caused eye strain, but that it was also portable and extremely convenient, factors to be weighed when considering what device to use for reading. Like earlier research (Rutherford et al, 2018; Twenge et al, 2019), the study found negative correlation between reading enjoyment and frequency with increased device usage, suggesting that for some students, technology was distracting from rather than supporting reading. As such, educators need to consider how to mitigate the effects of technology on reading for this profile of students.…”
Section: Discussionsupporting
confidence: 74%
“…Adolescents noted that the smartphone could be distracting and caused eye strain, but that it was also portable and extremely convenient, factors to be weighed when considering what device to use for reading. Like earlier research (Rutherford et al, 2018; Twenge et al, 2019), the study found negative correlation between reading enjoyment and frequency with increased device usage, suggesting that for some students, technology was distracting from rather than supporting reading. As such, educators need to consider how to mitigate the effects of technology on reading for this profile of students.…”
Section: Discussionsupporting
confidence: 74%
“…Based on the scores assigned to the answer options of reading format preference (online=1, print=2), we could argue that students were more inclined to read in print (M=2.16). Many studies showed that students preferred printed texts more than online materials (Keskin & Çetinkaya, 2017;Mizrachi et al, 20016;Rutherford, Singleton, Derr, & Merga, 2018;Spencer, 2006). On the other hand, several studies illustrated that adolescents preferred digital environments more (Duran & Alevli, 2014;Tveit & Mangen, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In order to increase digital inclusion, these stakeholders involve in interorganizational collaboration processes and carry out various initiatives aimed at solving this problem, such as the provision of universal access to the Internet and ICT, development of digital services and products, implementation of activities, oriented towards improvement of digital literacy skills and competences, etc. (Real et al 2016;Ragnedda 2018;Rutherford et al, 2018;Strover et al, 2020;Gann, , 2020Gallardo et al, 2020). Interorganizational collaboration is possible between stakeholders operating in the same, and in different spheres of the helix (Ilse, Leo 2012; Mehmood, Imran, 2021).…”
Section: Discussionmentioning
confidence: 99%